Billowing Light : Ishida Takashi (YASUDA Yoko; Seigensha Art Publishing, 2015)
Working in the field of experimental film, contemporary Japanese artist Ishida Takashi uses drawing animation techniques in his production, enabling him to shift between more traditional painting and the art of moving images. Using the body and physical action in combination with a variety of elements, such as music, architecture, light, and sound, he creates a chaotic space that is often difficult to comprehend and define. This book is published on the occasion of the first large-scale solo exhibition of his work, shown in Okinawa and Yokohama. Included are early and recent film and video installations, two-dimensional artworks related to these, and an interview with the artist.
Japanese; English
Keywords: N4390-5098 Visual Arts. Exhibitions